2015
DOI: 10.1111/tid.12356
|View full text |Cite
|
Sign up to set email alerts
|

Nosocomial bloodstream infections in a nationwide study: comparison between solid organ transplant patients and the general population

Abstract: Antimicrobial resistance is higher, particularly among gram-negative bacteria in the transplant population, although the overall mortality rate between transplant and non-transplant patients with nosocomial BSI is similar.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 23 publications
0
41
0
1
Order By: Relevance
“…In addition to these studies on XDR A baumannii, several other studies investigated carbapenem resistance in A baumannii and found it was quite common. 8,15,20,27,28 Carbapenem resistance in A baumannii in these studies ranged from 15.3% from Reddy and colleagues 27 to 75% from De Gouvea and colleagues. 8,15 Six studies investigated Pseudomonas aeruginosa.…”
Section: Prevalence Of Pathogens In Solid Organ Transplantmentioning
confidence: 92%
See 4 more Smart Citations
“…In addition to these studies on XDR A baumannii, several other studies investigated carbapenem resistance in A baumannii and found it was quite common. 8,15,20,27,28 Carbapenem resistance in A baumannii in these studies ranged from 15.3% from Reddy and colleagues 27 to 75% from De Gouvea and colleagues. 8,15 Six studies investigated Pseudomonas aeruginosa.…”
Section: Prevalence Of Pathogens In Solid Organ Transplantmentioning
confidence: 92%
“…8,15,20,27,28 Carbapenem resistance in A baumannii in these studies ranged from 15.3% from Reddy and colleagues 27 to 75% from De Gouvea and colleagues. 8,15 Six studies investigated Pseudomonas aeruginosa. 6,8,[20][21][22]24,30 Carbapenem resistance rates were high ranging from 18% 24 to 87.5%.…”
Section: Prevalence Of Pathogens In Solid Organ Transplantmentioning
confidence: 92%
See 3 more Smart Citations